Central Adiposity & the Functional Magnetic Resonance Imaging Response to Cognitive Challenge - Gonzales, Mitzi M. (2014)
BACKGROUND: Excessive adipose tissue, particularly with a centralized distribution, propagates hormonal and metabolic disturbance. The detrimental effects of adiposity may extend beyond the periphery and target the central nervous system, increasing vulnerability to cognitive decline. The aim of current study was to determine how central adiposity impacts the brain at midlife by examining the blood oxygen level-dependent (BOLD) response to a challenging cognitive task. METHODS: Seventy-three adults, aged 40-60 years, completed a 2-Back verbal working memory task during functional magnetic resonance imaging (fMRI). Central adiposity was assessed with waist circumference. The association between waist circumference and task-related activation in a priori regions of interest was modeled using bootstrapping regression models corrected for multiple-comparisons. RESULTS: Larger waist circumference was associated with diminished working-memory-related BOLD response in the right superior frontal gyrus (β=-0.008, p=0.001, 95% CI: -0.012 - -0.004) and left middle frontal gyrus (β=-0.009, p=0.002, 95% CI: -0.015 - -0.003), statistically adjusting for age, sex, systolic blood pressure, and total cholesterol. Reduced task-related activation in the right superior frontal gyrus (r=-0.369, p=0.002) and left middle frontal gyrus (r=-0.266, p=0.025) were related to slower reaction time on the task, controlling for age and education. CONCLUSIONS: Larger waist circumference predicted alterations in the BOLD response that coupled with decrements in task performance. While future studies are necessary, the results suggest that similar to its role in the periphery, central adiposity may be a robust predictor of metabolic and hormonal alterations that impinge upon central nervous system functioning.